2002
DOI: 10.1046/j.1526-0968.2002.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in the Peripheral Blood Leukocyte and Platelet Counts in Leukocytapheresis in Healthy Volunteers

Abstract: Leukocytapheresis (LCP) for the treatment of patients with diseases that involve an abnormal autoimmune reaction aims to improve the condition of the patient's pathology and to correct imbalances in immunological regulation mechanisms by removing the responsible leukocytes from the peripheral blood. To clarify the mechanism of therapeutic effect, LCP was conducted in healthy volunteers to investigate changes in peripheral blood leukocyte and platelet counts over time during the treatment. The subjects were 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 18 publications
7
46
0
Order By: Relevance
“…In our preliminary analyses of blood lymphocyteand monocyte-subsets using monoclonal antibodies against CD3, CD4, CD14, CD19, CD45RA, CD45RO, CD11a, CD11b, CD49d, CD62L, and IL-10 in RA patients, the post-LCAP/pre-LCAP ratios of the CD191 cell counts were consistently smaller than those of the CD31 cell counts (data not shown), in accordance with previous observations of LCAP in healthy volunteers [16].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our preliminary analyses of blood lymphocyteand monocyte-subsets using monoclonal antibodies against CD3, CD4, CD14, CD19, CD45RA, CD45RO, CD11a, CD11b, CD49d, CD62L, and IL-10 in RA patients, the post-LCAP/pre-LCAP ratios of the CD191 cell counts were consistently smaller than those of the CD31 cell counts (data not shown), in accordance with previous observations of LCAP in healthy volunteers [16].…”
Section: Discussionsupporting
confidence: 92%
“…Various proportions of metamyelocytes and myelocytes were found in the post-LCAP peripheral blood of the patients (0-1% and 0-4% respectively, of the total leukocyte counts), similar to the results of a previous study on LCAP in healthy volunteers [16].…”
Section: Blood Cell Kinetics and Neutrophil Dynamics In The First Lcasupporting
confidence: 88%
See 1 more Smart Citation
“…This is similar to the previous studies in patients with rheumatoid arthritis and ulcerative colitis and healthy volunteers (23)(24)(25). It has been reported that the peripheral blood platelets were removed while passing through the column (26).…”
Section: Discussionsupporting
confidence: 90%
“…During LCAP, most of the leukocytes are removed by a filter during extracorporeal circulation. This treatment is associated with rebound leukophilia in response to transient leukopenia (49,50), indicating a rapid cell release response from the reticuloendothelial system. Therefore, this drastic change in gene expression may be partly explained by the replacement of activated leukocytes with new and naïve ones originating from the marginated pool and/or bone marrow.…”
Section: Discussionmentioning
confidence: 99%